Complexities in the Determination of the General Will: A Critical Appraisal of Jean-Jacques Rousseau (Tamaddun, 2022)
The General Will is one of Jean-Jacques Rousseau’s original contributions to the district of political philosophy. The intellectual burden and herculean task of this inquiry consist of reconciling the General Will with the sanctity of individual freedom, which Rousseau also purports to protect. Through the method of philosophical and textual analysis, this paper examines the inherent absurdities, complexities, and obscurities associated with the determination and realisation of the General Will, which lie at the heart of, and are the nucleus of, the political philosophy of Rousseau. It further x-rays the acclaimed infallibility and veracity of this political theory vis-à-vis its claim as a moral norm—an authentic will that is ultimately right in its normative credentials. It adopts a qualitative research method, in which case, it is basically descriptive and highly analytical. It is significant as it provides a blueprint and a veritable guide for policymakers at all governance or social engineering levels. In conclusion, a case is made that, notwithstanding its manifold discontents and gross inadequacies, it is indeed a standard for enhancing distributive justice and the common good. It recommends that the doctrine of the General Will be made a guiding ideology and national philosophy and be incorporated into the federal character principle to address the lingering and looming challenges of Nigerian federalism against the backdrop of its fragile state structure. It also suggests that it be used as a criterion for establishing or gauging essential aims and guiding principles of state policy in the Nigerian political system.